Sulfurizing Sputtered-ZnO as buffer layer for cadmium-free Cu2ZnSnS4 solar cells. (October 2019) - Yang, Shuai; Wang, Shurong; Liao, Hua; Xu, Xin; Tang, Zhen; Li, Xinyu; Li, Xiang; Wang, Tingbao; Liu, Di
Abstract: In this work, Cadmium-free Zn(O, S) buffer layers were prepared by sulfurizing sputtered-ZnO films. The impacts of different annealing atmosphere and sulfurization temperatures on the properties of Zn(O, S) films were investigated. The sputtered-ZnO films were annealed at 150 °C for 30min under the air and oxygen gas atmosphere, and following sulfurized at 200 °C, 260 °C and 320 °C for 50min under the N2 atmosphere with sulfur powder, respectively. As a result, the ZnO films were annealed at 150 °C for 30min under O2 atmosphere and following sulfurized at 260 °C for 50min, which could obtain the best performance of Zn(O, S) film. The morphologies of Zn(O, S) films were more compact and uniform due to the reduction of oxygen loss. Meanwhile, the optimal sulfurization temperature could decrease the amounts of traps, which resulted in reducing the recombination and improving the transport of charge carriers. Finally, Cadmium-free Cu2 ZnSnS4 (CZTS) thin film solar cells with Zn(O, S) buffer layers were fabricated. The short circuit current density (Jsc ) and open circuit voltage (Voc ) of Zn(O, S)-based solar cells could be increased by improving the transmittance at short wavelength region and tuning the band offsets at Zn(O, S)/CZTS interface, and the best conversion efficiency was 5.11%. Highlights: The impacts of different annealing atmosphere and sulfurization temperatures on the properties of Zn(O, S) films were studied. The best properties of Zn(O, S) film was obtain at 150 °C for 30min under O2 atmosphere and sulfurized at 260 °C for 50min. The cadmium-free Zn(O, S) buffer layers were prepared by sulfurizing sputtered-ZnO films. The cadmium-free CZTS devices presented the best PCE of 5.11% with Voc of 610mV, Jsc of 21.18mA/cm 2 and FF of 39.53%.